(untitled) (Journal of Parents and Teachers, 2015)
This article presents bioethics as a link between science’s world and the humanities. Mainly it deals with all those aspects that are related to pain, suffering, grieving child that may occur in any school and therefore must be treated. All these aspects reflect the reality of education nowadays.